Rasio Keuangan, Financial Distress Perusahaan : Suatu Tinjauan - Afriyeni, Endang (Arthavidya Jurnal Ilmiah Ekonomi, 2013)
The tight competition requires every company in the country to be able to face competition both in the domestic and global markets. Financial statements issued as a source of information regarding the company's financial condition. Prediction of survival company is very important for the management and owners to anticipate the occurrence of financial distress leading to bankruptcy as measured through the analysis of the financial statements in the form of financial ratios.Keyword: competition, financial statement, financial distress, financial ratioPENDAHULUAN